Nutrient content in Quercus ilex canopies: seasonal and spatial variation within a catchment - Sabate, S; Sala, Anna; Gracia, C A (Plant and Soil, 1995)
Spatial and temporal changes in canopy nutrient content were studied in 1988 and 1989 in a Mediterranean Quercus ilex ssp. ilex L. forest in north-eastern Spain. Sampling was conducted in parallel at two sites which represent endpoints along a slope gradient within a small catchment (ridge top at 975 m and valley bottom at 700 m). Deeper soils resulted in significantly higher N and P concentrations, and N content on a leaf area basis at the valley bottom site. In contrast, K concentration in leaves was significantly higher at the ridge top site, where soil K concentration was also higher. At both sites, N and P content on a leaf area basis was highest at the top of the canopy, where leaf area is highest. N resorption efficiency decreased from top to bottom of the canopy. Results suggested a minor role of shaded leaves as nutrient storage sites. Lower P resorption efficiency was found at the ridge top site. Seasonal changes of P and N concentration on a leaf area basis suggest P replenishment, and to a lesser degree N, during periods of lower growth activity due to low temperatures, but coinciding with higher water availability (autumn-early spring period). Thus, N and P resorption from the remaining foliage in the canopy took place, and to a larger degree at the valley bottom site, coinciding with a slightly higher leaf area index and productivity at this site.
Keywords: Canopy; nutrient content and dynamics; nutrient resorption; Quercus ilex